2020
DOI: 10.1007/s13596-020-00508-9
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase inhibitors identified from Camellia sinensis for COVID-19 prophylaxis: an in silico approach

Abstract: To respond to the public panic, government and private research organizations of every country keep working on the COVID-19 pandemic, even though still there is a lack of more efficacious medicine for the choice of Coronavirus disease treatment. To counteract on this situation several approved drugs including anti-malarial (hydroxychloroquine and chloroquine), and few anti-viral (remdesvir) agents are choice of treatment for COVID-19. However, these agents suffer from certain limitation in their uses and point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
0
14
0
2
Order By: Relevance
“…The MMPs are a group of proteases directly associated with inflammatory cytokines/chemokines ( e.g. IL-6) [65] , [66] , [67] , [68] , [69] . Based on the assessments, the plasma level of MMP-9 in patients with COVID-19 has been higher than in the control group from the earliest days of hospitalization and has culminated along with the disease progress.…”
Section: Sars-cov-2 and Pro-inflammatory Pathwaysmentioning
confidence: 99%
“…The MMPs are a group of proteases directly associated with inflammatory cytokines/chemokines ( e.g. IL-6) [65] , [66] , [67] , [68] , [69] . Based on the assessments, the plasma level of MMP-9 in patients with COVID-19 has been higher than in the control group from the earliest days of hospitalization and has culminated along with the disease progress.…”
Section: Sars-cov-2 and Pro-inflammatory Pathwaysmentioning
confidence: 99%
“…Further, molecular docking analysis revealed that five bioactive polyphenols of Camellia sinensis viz. theaflavin, epigallocatechin 3-gallate, genistein, 1-O-caffeoylquinic acid and ethyl transcaffeate showed affinity against matrix metalloproteinase (MMPs) against SARS-CoV-2 main protease [198]. Among these five polyphenolic compounds, theaflavin and epigallocatechin 3-gallate showed strong affinity and good drug likeness score and could be beneficial option in the prophylaxis of COVID-19 outbreak [198].…”
Section: Anti-viral Potential Of Camellia Sinensismentioning
confidence: 99%
“…theaflavin, epigallocatechin 3-gallate, genistein, 1-O-caffeoylquinic acid and ethyl transcaffeate showed affinity against matrix metalloproteinase (MMPs) against SARS-CoV-2 main protease [198]. Among these five polyphenolic compounds, theaflavin and epigallocatechin 3-gallate showed strong affinity and good drug likeness score and could be beneficial option in the prophylaxis of COVID-19 outbreak [198]. In consistent to this, a similar study suggested that EGCG and theaflavin mainly theaflavin-3, 3'-digallate (TF3) showed significant interaction with the receptor binding domain of SARS-CoV-2 [199].…”
Section: Anti-viral Potential Of Camellia Sinensismentioning
confidence: 99%
“…The SARS-CoV-2 inhibitory effect of Indian ginseng was proven in silico by Chikhale et al [ 95 ]. The matrix metalloproteinase inhibitors identified from Camellia sinensis showed M pro inhibition [ 96 ]. The computational studies proved that the bioactive compounds had a significant effect on SARS CoV-2.…”
Section: Main Textmentioning
confidence: 99%